Penentuan Siswa Berprestasi Dengan Penerapan Metode Analytical Hierarcy Process - Feqo Putra Ajiansya; Ani Oktarini Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Education plays a very important role in improving the quality of human resources and improving the standard of living of the Indonesian people, as well as the role of students. SDN Malaka Sari 04 (Elementary School) is a coaching task for students from the age of 7 years to help the development of students so that they are ready to go to the next level. SDN Malaka Sari 04 is an elementary school that also has good achieving students. Determining outstanding students at SDN Malaka Sari 04 using the criteria of knowledge value, skill value and attitude value. The problem in selecting outstanding students is that there is no method to determine the priority of many criteria and there is no weighting for each criterion. This results in inaccurate assessment results. SDN Malaka Sari 04 uses these criteria to determine whether the student is advancing to a grade or not. The system used is the analytical hierarchy process (AHP) method. Data was collected by means of interviews, observations and literature studies. From these results, it is obtained that the ranking scores for outstanding students include: Kelvin Apriansyah ranks 1 with a value (25.17%), Achmad Ibrahim ranks 2nd with a value (21.37%), Putri Fauziah occupies ranked 3rd with a value of (19.21%), Iftikhoirul Akhyar ranked 4th with a value of (18.16%), and lastly Tisya Farista ranked 5th with a score (16.09%). Data processing was carried out using one of the, namely the Analytical Hierarchy Process (AHP) method, with the result that Kelvin Apriansyah was determined as the best achieving student.